Bacterial and clinical profile of diabetic foot ulcer using optimal culture techniques - Patil, Swati V.; Mane, Roshan R. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetic foot ulcers (DFU) are the complications of diabetes mellitus. The diabetic foot ulcer infections are polymicrobial in nature. If they are not recognized and controlled it leads to many devastating consequences like limb amputation, sepsis, and even mortality. Hence, the present study was undertaken to determine the bacterial and clinical profile of diabetic foot ulcer using optimal culture techniques and the antimicrobial sensitivity pattern of the isolates. Methods: A total number of 103 patients with a foot ulcer of Wagner’s grade II or more and evidence of purulent exudates or edema were included in the study. Swab samples were obtained from the base of ulcers and were sent for bacteriological study. The specimen was processed in the microbiology laboratory for Gram stain, aerobic culture, and anaerobic culture. The organisms isolated were identified by standard procedures and antimicrobial susceptibility was done by Kirby-Bauer disc diffusion method. Results: A total no of 253 organisms were isolated from 103 patients. Out of these, 217 aerobes were isolated, and the most common organism isolated from gram positive bacteria was Staphylococcus aureus, 53 (24.42 %). Pseudomonas aeruginosa, 42 (19.35 %) was the predominant organism isolated from gram negative bacteria. Among the total 36 anaerobes, Bacteroides fragilis group, 17 (47.22 %) was the most common organism isolated. All the gram positive aerobic organisms were found to be sensitive for vancomycin. Among the gram negative organisms, E. coli, Proteus mirabilis, Proteus vulgaris, showed more sensitivity to cefotaxime (90.62%, 91.66%, 75%) respectively. Metronidazole was the drug of choice in case of anaerobes followed by imipenem. Conclusions: It is necessary to identify the etiological factors and susceptible microorganisms responsible for causation of DFU. So that prompt management of diabetic foot ulcers is possible for successful outcome. Appreciation of the causative organisms in diabetic foot and their antibiotic sensitivity is essential for institution of appropriate antibiotic therapy.